2010
DOI: 10.4025/actasciagron.v32i4.5445
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade espacial e temporal de plantas daninhas em Latossolo Vermelho argiloso sob semeadura direta

Abstract: RESUMO. O conhecimento da variabilidade espacial das plantas daninhas permite açôes de manejo localizado, que podem trazer o duplo beneficio da economia de insumos e da preservacáo da qualidade do amhiente. Este trabatho objetivou avaliar a distrihuiçâo espacúil de plantas daninhas num Latossolo Vermelho distrófico (LVd) argiloso em Campinas, Estado de Sao Paulo, no periodo entre 2003 e 2008. A área amostrada era de 3,42 hectares e apresentava 302 pontos amostráis distribuidos em grade regular de 10 x 10 m. Os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 19 publications
5
13
0
6
Order By: Relevance
“…These results were similar to those found by Chiba et al (2010) when mapping the spatial variability of weeds using precision farming tools using 10 x 10 m cells, divided into three classes of infestation, who concluded that there was a defined spatial dependency structure for plants separated according to the type of leaf and for their total number. The maps obtained in this study show the aggregated pattern of spatial distribution of weeds.…”
Section: Resultssupporting
confidence: 78%
“…These results were similar to those found by Chiba et al (2010) when mapping the spatial variability of weeds using precision farming tools using 10 x 10 m cells, divided into three classes of infestation, who concluded that there was a defined spatial dependency structure for plants separated according to the type of leaf and for their total number. The maps obtained in this study show the aggregated pattern of spatial distribution of weeds.…”
Section: Resultssupporting
confidence: 78%
“…High CV values are commonly associated with counting data, and reflects the variability of the number found point-to-point (Chiba et al 2010). Therefore, high CV values observed in this study suggest high data variability of the E. heros infestation in the area (Oliveira et al 2015), requiring the use of sampling plans with higher number of samples to efficiently reproduce this spatial variability in unsampled locals.…”
Section: Methodsmentioning
confidence: 94%
“…Several studies of pest population dynamics have reported that, under low infestation, the data do not follow a normal distribution curve (Reay-Jones et al 2010;Riffel et al 2012;Carleton et al 2013). In this case, using conventional sampling protocols, which takes into account the arithmetic mean value, non-normal data do not represent satisfactorily the variability of the insect population in the field (Chiba et al 2010). On the other hand, data normality is not a requirement of geostatistical analysis; however, asymmetric distributions with high number of outliers deserve attention (Webster and Oliver 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jaremtchuk et al (2008) emphasize that the mapping of weed population allows the monitoring of the infestation over time, enabling the development of management strategies that minimize the effect of competition with the crop, besides the saving of resources due to the application of varying volumes according to the infestation. Chiba et al (2010), studying spatial and temporal variability of weeds in a Red Latosol with clayey texture under notillage system, observed that weeds, both magnoliopsida and liliopsida, show a defined spatial distribution structure (nonrandom occurrence), allowing the use of geostatistical analysis to fit theoretical models of semivariance and construction of thematic maps. These authors also pointed out that the mapping of weeds indicated an aggregated structure of occurrence (localized groups), which may favor the localized application of herbicides, corroborating with studies conducted by Wiles & Brodhal (2004), who demonstrated that the spatial distribution pattern of weeds rarely occurs at random, because it is conditioned to the specific differences of each environment.…”
Section: Introductionmentioning
confidence: 99%